GIS APPLIED TO THE STUDY OF TEMPORAL RECOVERY OF BURNED AREAS IN THE MUNICIPALITY OF PAI PEDRO LOCATED IN REGION NORTH OF THE STATE OF MINAS GERAIS - Nascimento, Cristina Rodrigues (Journal of Hyperspectral Remote Sensing, 2013)
The northern region of Minas Gerais is considered a transition area between the biomes Caatinga and Savanna, with predominance of the Savanna and its variations. It is common to the occurrence of fires, which can be caused naturally or by anthropogenic actions, resulting in changes in the landscape. In this sense, the study aims to evaluate from time series of LANDSAT-5/TM and MODIS/TERRA images the process of natural recovery of vegetation after the identification of operational pixels corresponding to the burned areas. The results of the research are based on the response of the municipality test of Pai Pedro/MG. We can observe that was detected a hotspots pixel on the day 08/04/2008 through images MOD14A1, which validation was performed from the survey of burned areas conducted by INPE - National Institute of Space Research. From the identification of operational pixel of burned was evaluated the dynamics of recovery of the area through the vegetation index NDVI (Normalized Difference Vegetation Index), generated by images MODIS/TERRA, product MOD13Q. The scars of burned analyzed, approximately 52% were detected. Despite this limitation, much of the area impacted was identified. The errors of omission were considered satisfactory, with a view to the technical limitations of spatial resolution of the sensors used.